If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5t + -6 = 42 + -1t Reorder the terms: -6 + 5t = 42 + -1t Solving -6 + 5t = 42 + -1t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add 't' to each side of the equation. -6 + 5t + t = 42 + -1t + t Combine like terms: 5t + t = 6t -6 + 6t = 42 + -1t + t Combine like terms: -1t + t = 0 -6 + 6t = 42 + 0 -6 + 6t = 42 Add '6' to each side of the equation. -6 + 6 + 6t = 42 + 6 Combine like terms: -6 + 6 = 0 0 + 6t = 42 + 6 6t = 42 + 6 Combine like terms: 42 + 6 = 48 6t = 48 Divide each side by '6'. t = 8 Simplifying t = 8
| m-6=m | | 2x=(7x-y)+(6-4y) | | 6-2(w+1)=6w-2(6+w) | | 7(s-4)+13= | | .47=log(x) | | 0.11x=56 | | 5-x=8-x-3 | | 4x-17=4x | | 16=4(1+7x)-8(3x-5) | | f=6/5(n-18) | | 8-3(2x+3)=11 | | 4x-5=4x+12 | | -3(2x+3)=11 | | g=5/3(p-49) | | 4-5-13-18+2= | | 14=8x+7-x | | 458000*9= | | ln(x-4)=6 | | 90=2(7x+3) | | 3x+5x-8+4-11+17x-42+7x=-6 | | -252=-7(-6x+6) | | -91=-7(3r+4) | | 8w-14=434 | | 3(-5x+2)=-84 | | 6x+27=36 | | 7x+9y=103 | | 2x^2+-2x^2= | | (5y+3)(1+y)=0 | | (x-3)-2=6-2(x-1) | | -126=-3(-6-8n) | | -18-3p=-(p+4) | | 9y^3-11x^2+2-13y^3-15x^2= |